Performance of medicinal plants and soil fertility under Bambusa nutans-based agroforestry system - Lakra, Sumit; Dr. Prabhat Ranjan Oraon; Singh, Bijay Kumar (Indian Journal of Agroforestry, 2025)
A field experiment was conducted to evaluate the growth of bamboo and yield of medicinal plant under bamboo-based agroforestry system at Birsa Agricultural University Kanke, Ranchi Jharkhand. The experiment comprised with seven treatments viz.,T1: Bamboo + Kalmegh; T2: Bamboo + Ashwagandha; T3: Bamboo + Sadabahar; T4: Sole Bamboo; T5: Sole Kalmegh; T6: Sole Ashwagandha and T7: Sole Sadabahar. The experiment was laid out in a randomized block design with three replications. The results revealed that maximum culm height increment has been noted in T4: Sole Bamboo 2.84 m followed by T3: Bamboo + Sadabahar which was 2.81 m, and T1: Bamboo + Kalmegh which was 2.50 m and minimum average culm height increment recorded in T2: Bamboo + Ashwagandha which was noted to be 2.25 m. Maximum increment in diameter of 5th internode growth of bamboo was seen in T4: Sole Bamboo 0.45 cm followed by T3: Bamboo + Sadabahar 0.38 cm andT1: Bamboo + Kalmegh 0.37 cm and minimum found in T2: Bamboo + Ashwagandha 0.29 cm. Net Return as compared to sole treatments viz., T3: Bamboo + Sadabahar Rs. 40,557.60 ha-1 followed by T2: Bamboo + Ashwagandha Rs. 35,791.20 ha-1, T1: Bamboo + Kalmegh Rs. 34,144.18 ha-1, T4: Sole Bamboo Rs. 26,459.00 ha-1, T7: Sole Sadabahar Rs. 17,633.60 ha-1, T6: Sole Ashwagandha Rs. 11,930.00 ha-1 and T5: Sole Kalmegh Rs. 9,285.18 ha-1 recorded lowest. Sole crops gave more benefit: cost ratio as compared to Combination crops. T7: Sole Sadabahar with 3.52 followed by T6: Sole Ashwagandha 1.83, T5: Sole Kalmegh 1.54, T3: Bamboo + Sadabahar 1.66, T4: Sole Bamboo 1.34, and minimum was under T1: Bamboo + Kalmegh and T2: Bamboo + Ashwagandha both 1.32.